Economic evaluation of intellectual products - Pererva, P. G.; Kosenko, S. A.; Kobіelіev, I. V. (Харківська державна наукова бібліотека імені В. Г. Короленка, 2024)
The report discusses modern methods and approaches to determining the value of intangible assets, such as patents, copyrights, trademarks and other intellectual products. The report highlights the importance of economic valuation of intellectual products in today's digital economy, where these assets are becoming a major source of value for companies. An overview of traditional valuation methods is presented, as well as innovative approaches that take into account the impact of new technologies, such as artificial intelligence and blockchain. The main conclusions of the work include recommendations for improving the practices of evaluating intellectual products to increase their efficiency and accuracy.

Розглянуто сучасні методи та підходи до визначення вартості нематеріальних активів, таких як патенти, авторські права, торгові марки та інші інтелектуальні продукти. Підкреслено важливість економічної оцінки інтелектуальних продуктів у сучасній цифровій економіці, де ці активи стають основним джерелом вартості для компаній. Представлено огляд традиційних методів оцінки, а також запропоновано інноваційні підходи, що враховують вплив нових технологій, таких як штучний інтелект і блокчейн. Висновки роботи містять рекомендації щодо вдосконалення практик оцінки інтелектуальних продуктів для підвищення їхньої ефективності та точності.
Економічна оцінка інтелектуальних продуктів
Keywords: intellectual property; valuation; methods; law; інтелектуальна власність; вартісна оцінка; методи; право